Stability of cypermethrin against a prepared high surface area magnesium oxide - Mohd. Yusoff, Hanis (2006)
High surface area magnesium oxide was prepared by various methods of preparation using modified dehydration technique. Commercial magnesium oxide was first transformed into its hydroxide. The magnesium hydroxide was heated under high vacuum at different temperatures of 200, 400, 600 and 800 degree Celsius and high surface area magnesium oxide was obtained. The activated magnesium oxide sample was labeled as dehydrated magnesium oxide. The same magnesium hydroxide was also calcined at various temperatures and was labeled as dehydrated and calcined magnesium oxide. Finally, the third magnesium oxide sample was labeled as magnesium oxide sol gel, produced by synthesis of Mg turnings to form sol gel solution and was dried using autoclave which will convert to its magnesium hydroxide sol gel. Again, activation using high vacuum will convert magnesium hydroxide sol gel into its high surface area magnesium oxide. To characterize the resulting magnesium oxide samples, several spectroscopic techniques were used which includes Fourier Transform Infra-Red, X-Ray Diffraction, Nuclear Magnetic Resonance and Electron Spin Resonance. For better understanding of the magnesium oxide surface area and morphology, Nitrogen Gas Adsorption and Scanning Electron Microscope, was used. Pyrethrin is the most effective insecticide. However it is not harmful to mammals or humans. Synthetic pyrethroid that is cypermethrin later was developed. Since cypermethrin was sprayed towards furnitures, floors, walls at home and at the agriculture field, thus their stability towards these matrices is important. In this study, the stability of cypermethrin under variously prepared high surface area magnesium oxide effect was studied using Fourier Transform Infra-Red spectroscopy and Gas Chromatography with Electron Capture Detector. For comparison, inert matrix of activated carbon was used.